2016
DOI: 10.1093/mnras/stw1363
|View full text |Cite
|
Sign up to set email alerts
|

Early science with the Large Millimetre Telescope: Deep LMT/AzTEC millimetre observations of ϵ Eridani and its surroundings

Abstract: ǫ Eridani is a nearby, young Sun-like star that hosts a ring of cool debris analogous to the solar system's Edgeworth-Kuiper belt. Early observations at (sub-)mm wavelengths gave tentative evidence of the presence of inhomogeneities in the ring, which have been ascribed to the effect of a putative low eccentricity planet, orbiting close to the ring. The existence of these structures have been recently challenged by high resolution interferometric millimeter observations. Here we present the deepest single-dish… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 53 publications
5
39
3
Order By: Relevance
“…We found that a central ring with a radius of ∼13 au and an outer ring peaked at 64 au with a width of ∼24 au can fit the observed radial profile relatively well (red line in Figure 5). It is reassuring that the peak position of the outer ring is found to be similar to the location found in other studies (∼64 au, Backman et al 2009;MacGregor et al 2015;Chavez-Dagostino et al 2016). However, as in the 35 μm profile analysis, this does not indicate there is only one inner excess region, but only that the inner excess emission region is extended at least to ∼13 au.…”
Section: Excess Emission At 24 M Msupporting
confidence: 88%
See 1 more Smart Citation
“…We found that a central ring with a radius of ∼13 au and an outer ring peaked at 64 au with a width of ∼24 au can fit the observed radial profile relatively well (red line in Figure 5). It is reassuring that the peak position of the outer ring is found to be similar to the location found in other studies (∼64 au, Backman et al 2009;MacGregor et al 2015;Chavez-Dagostino et al 2016). However, as in the 35 μm profile analysis, this does not indicate there is only one inner excess region, but only that the inner excess emission region is extended at least to ∼13 au.…”
Section: Excess Emission At 24 M Msupporting
confidence: 88%
“…The large cold ring at 64 au is confirmed in the millimeter (Lestrade & Thilliez 2015;MacGregor et al 2015). From these images, it appears that many of the clumps can be ascribed to chance alignment with background galaxies (Chavez-Dagostino et al 2016).…”
Section: Introductionmentioning
confidence: 70%
“…VLA source 6 coincides with Eridani. Finally, VLA source 11 coincides within ∼2 with millimeter source 5 in the list of Chavez-Dagostino et al (2016). the distance of Eridani) and that this comparison rules out the possibility that the radio emission is coming from a position displaced more than 0.2 AU from the star.…”
Section: Field Sources At 10 Ghzsupporting
confidence: 57%
“…Assuming the two sources are physically not related, the chance of both within 4 of the star is 0.06%. The contamination from multiple background point sources is also seen around Eri (Chavez-Dagostino et al 2016). Therefore, it is possible that the sources in HD 95086 are related background galaxies, and the 0.06% probability is then a lower limit.…”
Section: Alignment Of a Background Galaxymentioning
confidence: 99%